The Relationship of Hemoglobin, Interleukin-10 and Tumor Necrosis Factor Alpha Levels In Asymptomatic Malaria Patients in Trenggalek, Jawa Timur, Indonesia - Arif Rahman Nurdianto; Heny Arwati; Yoes Prijatna Dachlan; Dyah Ayu Febiyanti (Molecular and Cellular Biomedical Sciences, 2019)
Background: Malaria is still a universal health problem, especially in tropical countries because of high morbidity and mortality rates. Infection by Plasmodium falciparum and Plasmodium vivax could result in asymptomatic disease of malaria and be found in Trenggalek, Jawa Timur. Differences in pathogenesis among affected individuals are affected by many factors, and the immune system is one of them. Among substances involved in the malarial immunity is Tumor Necrosis Factor (TNF)-α and Interleukin (IL)-10, produced by the body's defense system as the reaction to the parasite. Therefore a study was designed to detect the level of TNF-α and IL-10 in asymptomatic malaria patients.Materials and Methods: A cross-sectional study was conducted. Thirty male asymptomatic malaria subjects, age 21 to 60 years were selected. Blood from each subject was collected and the levels of TNF-α and IL-10 were analyzed using enzyme-linked immunosorbent assay (ELISA) method. Significant values considered at p<0.05.Results: There was an increased level of TNF-α with the average of 218.760 pg/µL, and an increased level of IL-10 with an average of 257.574 pg/µL in asymptomatic malaria subjects. In normal person IL-10 level is 12.6 (8.5-16.7) pg/mL and the levels of TNF-α in normal person is 0-1.5 pg/mL because they are not produce. There was a positive correlation of TNF-α with IL-10 (r=0.332; p>0.05), and positive correlation between TNF-α and the rate of hemoglobin (r=0.002; p>0.05). IL-10 was correlated negatively with the rate of hemoglobin (r=-0.363; p<0.05).Conclusion: The results from this study conclude that TNF-α and IL-10 levels increase in asymptomatic malaria subjects.Keywords: asymptomatic malaria, TNF-α, IL-10, parasite, hemoglobin